Do Young People Adapt Their Prosocial Behaviour to That of Their Peers? An Experimental Exploration. (September 2019) - Salgado, Mauricio; Vásquez, Alejandra; Yáñez, Alejandra
Moral decisions – that is, decisions that consider the consequences for the welfare of others – can be highly inconsistent across contexts. Here, we explore whether the altruism of young people is related to their willingness to cooperate with others, even in groups comprising non-reciprocating peers. Using the distinction between normative and cognitive expectations, we address this topic conducting several lab-in-the-field experiments with high-school students who played the dictator and linear public good games. We found that the altruism of young people in the dictator game and cooperation in the public good game were related, but only in the first rounds of the public good game. This indicates that young people orient their prosocial behaviour based on cognitive expectations, that is, they consider the information they receive regarding the free riding behaviour of peers and adapt their own. Nonetheless, young people who demonstrated high altruism tended to cooperate unconditionally, regardless of whether they belonged to a cooperative or uncooperative group, and despite disappointments. Finally, self-regarding young people were less likely to defect among cooperative peers. Therefore, group characteristics provide the boundary conditions for the consistency of the prosocial behaviour of young people. Some conceptual and policy implications are discussed.